Unbundling the Relationship between Economic Shocks and Crime - Eduardo Ferraz; Rodrigo R. Soares; Juan Vargas (Institute of Labor Economics (IZA), 2021)
Intuitively, by increasing the opportunity cost of engaging in criminal activities, positive economic shocks should reduce crime. However, the empirical evidence on the relationship between economic shocks and criminal behavior is at best ambiguous. This may be because certain types of shocks make the booty more attractive and thus constitute an incentive to predate. Beyond this basic distinction between an "opportunity cost" and a "rapacity" mechanism that may mediate the effect of economic shocks on crime, this chapter proposes a simple conceptual framework to understand this nuanced relationship. We posit that the way that economic shocks shape criminal behavior depends on three factors: i) whether the shock comes from a legal or an illegal source, ii) the extent to which the shock source is more or less lootable, and iii) the presence of contextual factors that shape the relative importance of the opportunity cost and the rapacity effect, such as the underlying level of economic inequality, the institutional strength and law enforcement capacity of the state, and whether there are instances of accelerated and hazardous economic growth that likely create social disorganization and institutional unbalance. We use this taxonomy to review the seemingly inconclusive empirical evidence, and close by highlighting current persisting puzzles as well as areas where additional research on the relationship between economic shocks and crime would be welcome.
Keywords: K42; J30; D74; F16; 330; economic shocks; crime; opportunity cost; rapacity; illegal activity; inequality; institutions; social disorganization